(untitled) (Web of Discoveries: Journal of Analysis and Inventions, 2026)
In this study, a tin dioxide (SnO₂)-based metal oxide film was deposited on a silicon (Si) substrate using the spray–pyrolysis technique of the sol–gel method. The influence of isothermal annealing on the structural and electrical properties of the obtained films was investigated, demonstrating that this treatment enhances the operational stability of the sensor. For SnO₂ metal oxide materials, the most critical and informative parameter is electrical conductivity (or resistivity), as even small variations in the analyzed gas concentration cause significant changes in the film’s electrical resistance. The results indicate that SnO₂-based gas sensors exhibit high sensitivity to gases such as hydrogen sulfide (H₂S), freons, ethanol vapors, chlorine vapors, and hydrogen (H₂). For these gases, the sensors’ sensitivity, operating temperature, and electrical characteristics were determined, allowing an assessment of their potential practical applications. The findings demonstrate that SnO₂ metal oxide films are promising candidates as gas-sensing elements for environmental monitoring and industrial safety systems.